Pengaruh Model Pembelajaran Game Based Learning Berbantuan Media Lumio terhadap Motivasi dan Hasil Belajar Siswa Kelas VII SMP Negeri 9 Samarinda - Sapan, Angellya Kristin; Turista, Dora Dayu Rahma; Maasawet, Elsje Theodora; Purwati, Sri; Makkadafi, Suparno Putera; Rambitan, Vandalita Maria Magdalena (Biocaster : Jurnal Kajian Biologi, 2025)
The Game Based Learning learning model is a learning approach that uses game elements in the learning process that involves students so that students interact more and play an active role during the learning process in the classroom. The use of the Game Based Learning Model is complemented by the use of Lumio as a learning medium. Lumio is a digital-based learning platform that combines slide presentations with activities such as quizzes and games, creating an active, fun and effective learning process in the modern technological age. The success of the learning process in the classroom is largely determined by appropriate teaching strategies and approaches. The purpose of this study is to determine the influence of the Game Based Learning model assisted by Lumio media on student motivation and learning outcomes in Science Class VII subjects of SMP Negeri 9 Samarinda. The method used in this study is a Quasi experiment which was designed using the Nonequivalent Control Group Design. The data analysis technique used was an independent sample test on the Mann Whitney non-paramteric test with the use of the Lumio-assisted Game Based Learning learning model on Motivation and The results showed that there was a significant difference between the experimental and control classes, with a sig value. 2-tailed 0.000 < 0.05, so from the Mann Whitney test it is known that there is an influence on the application of the Game Based Learning learning model assisted by Lumio media on student motivation and learning outcomes in science subjects grade VII SMP Negeri 9 Samarinda.